2020
DOI: 10.1111/cas.14316
|View full text |Cite
|
Sign up to set email alerts
|

ALDH1A3‐mTOR axis as a therapeutic target for anticancer drug‐tolerant persister cells in gastric cancer

Abstract: Tumors consist of heterogeneous cell populations that contain cancer cell subpopulations with anticancer drug‐resistant properties called “persister” cells. While this early‐phase drug tolerance is known to be related to the stem cell‐like characteristic of persister cells, how the stem cell‐related pathways contribute to drug resistance has remained elusive. Here, we conducted a single‐cell analysis based on the stem cell lineage‐related and gastric cell lineage‐related gene expression in patient‐derived gast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 36 publications
0
31
0
Order By: Relevance
“…While short-term changes are often phenotypic in nature and involve foraging of the phenotypic landscape, long-term survival strategies may involve genomic changes to enable being trapped in the "attractors" explored during short-term foraging. While such transitions to a persister (reversibly resistant) cell state have been largely associated with epigenetic reprogramming (2), recent studies show significant variation in transcriptional programme of such cells too as compared to sensitive cells from the same genetic background (48,(55)(56)(57), suggesting a critical role of transcriptional regulation in the emergence of reversible therapy-resistance (i.e. persistence), a "bet-hedging" strategy to ensure survival in time-and/or space-varying environments (54).…”
Section: Discussionmentioning
confidence: 99%
“…While short-term changes are often phenotypic in nature and involve foraging of the phenotypic landscape, long-term survival strategies may involve genomic changes to enable being trapped in the "attractors" explored during short-term foraging. While such transitions to a persister (reversibly resistant) cell state have been largely associated with epigenetic reprogramming (2), recent studies show significant variation in transcriptional programme of such cells too as compared to sensitive cells from the same genetic background (48,(55)(56)(57), suggesting a critical role of transcriptional regulation in the emergence of reversible therapy-resistance (i.e. persistence), a "bet-hedging" strategy to ensure survival in time-and/or space-varying environments (54).…”
Section: Discussionmentioning
confidence: 99%
“…Apart from vitamin A metabolism, the importance of ALDH and ADH were demonstrated in cancer cell proliferation, motility and metastasis [28] [29], due to their speci c role in affecting mTOR dependent signalling. In a previous study it has been revealed that ALDH1A3 downregulation directly affects mTOR expression and its downstream signals via S6K [30]. Result that ALDH1A3 mRNA was signi cantly upregulated in TSC2-/-S102 and patient derived LAM lung cell lines that leads to mTOR activation and downregulation of RARβ expression [6] was con rmed by immuno uorescent staining ( Figure 1D) and western blotting ( Figure 1E).…”
Section: Resultsmentioning
confidence: 64%
“…An elegant work recently using whole-genome RNAi screening identified MTOR as a common orchestrator in stress-induced genomic instability, accelerating the adaptation of cancers in cytotoxic condition and facilitating the cancer resistance to different oncotherapy (44). Moreover, the combination of 5-FU and temsirolimus, an mTOR inhibitor, reduced the chemoresistance related persister cells in gastric cancer (8). Besides TP53 and MTOR mediated lower proliferation, wnt/beta-catenin signaling was revealed here to be associated with higher survival potential.…”
Section: Discussionmentioning
confidence: 99%
“…It was estimated that 20% of DTPs could eventually revert to proliferative state and develop to "drug-tolerant expanded persisters" (DTEPs) (5,7). The slow-cycling state of DTP was recognized as the precondition for further transcriptional reprogramming on the way to DTEPs (8,9). Compared with parental cells, DTPs exhibited an increased dependency on main anti-apoptotic effectors, BCL-2, and BCL-XL, which might be regulated through ER stress signaling (10,11).…”
Section: Introductionmentioning
confidence: 99%